Precision of geoid approximation and geostatistics: How to find continuous map of absolute gravity data - Song, Hongzhi (2015)
An accurate geoid model is needed for surveyors and engineers who require orthometric heights on a common datum, and environment scientists who require elevations relative to present sea level. Airborne gravity data has been collected by the National Geodetic Survey (NGS) under the Gravity for the Redefinition of the Amer- ican Vertical Datum (GRAV-D) project and is available along the coasts of the Gulf of Mexico. For this study we obtained a set of absolute gravity data derived from full-field gravity at altitude/elevation. We used the data to derive free-air gravity anomalies to establish gravity on the geoid. For spatial interpolation we used the kriging method to estimate gravity on the geoid in any location and kriging of the difference between gravity on the ellipsoid of reference and the geoid. Various kriging methods were used for evaluation of errors calculated in this study. The mean precision of the predicted values is around 1.23 cm, a very good result for coastal regions, which traditionally have sparse gravity data sets.